Shadow economies around the world: what do we know? - Friedrich Schneider; Robert Klinglmair (Johannes Kepler University of Linz, Department of Economics, 2004)
Using various statistical procedures, estimates about the size of the shadow economy in 110 developing, transition and OECD countries are presented. The average size of the shadow economy (in percent of official GDP) over 1999-2000 in developing countries is 41%, in transition countries 38% and in OECD countries 18.0%. An increasing burden of taxation and social security contributions combined with rising state regulatory activities are the driving forces for the growth and size of the shadow economy. If the shadow economy increases by one percent the annual growth rate of the official GDP of a developing country (of a industrialized and/or transition country) decreases by 0.6% (increases by 0.8 and 1.0 respectively).
Keywords: O17; O5; D78; H2; H11; H26; 330; shadow economy; interaction of the shadow economy with the official one; tax burden; Schattenwirtschaft; Steuerbelastung; Schätzung; OECD-Staaten